Determinan Kemiskinan di Wilayah Kepulauan: Peran Pertumbuhan Ekonomi, Pembangunan Manusia, dan Belanja Pemerintah di Provinsi Maluku - Maximiliane Leonora Cornelia Hukom; Samie Lambert Jacobs (Univiversitas Dr. Djar Wattiheluw, 2025)
Poverty remains a major development challenge, particularly in geographically fragmented regions such as Maluku Province, Indonesia. This study examines the effects of economic growth, the Human Development Index (HDI), and government expenditure on poverty levels across 11 regencies/cities in Maluku Province during 2019–2023. Using a quantitative approach, this study applies panel data regression analysis estimated through the appropriate model selection procedures. The findings reveal that economic growth, HDI, and government expenditure significantly influence poverty reduction. However, the positive relationship between economic growth and poverty indicates that economic expansion has not yet generated inclusive benefits for vulnerable groups. Similarly, improvements in human development have not been fully transformed into productive employment opportunities and income enhancement. Government expenditure demonstrates an important role in reducing poverty through public investment and social development programs. These findings highlight the importance of integrated policies that combine inclusive economic growth, human capital development, and effective fiscal management to achieve sustainable poverty reduction in island regions.